"Have a little less, feel a lot better": Mixed-method evaluation of an alcohol intervention. (December 2020) - Lockwood, Nina; de Visser, Richard; Larsen, John
Highlights: A multimedia campaign encouraging men to drink less produced changes in alcohol use. Men appreciated the straightforward message and friendly tone of the campaign. There is also a need to develop the necessary behavioural skills for behaviour change. Abstract: The aim of the mixed-methods study reported here was to evaluate the impact of a "gain-framed", multimedia campaign to encourage heavier drinking men aged 45–64 years to drink less. Quantitative analyses were based on pre-intervention panel surveys of 3057 men in intervention regions and 500 in the control region, and post-intervention panel surveys of 1508 men in intervention regions and 219 in the control region. Qualitative analyses entailed thematic analysis of interviews with 14 men: five who had reduced their drinking after seeing the campaign, four who had considered reducing but did not, and five who did not consider changing. Interviews focused on men's responses to the campaign, and their ideas for how to improve it. In quantitative analyses, the campaign was associated with significant changes in alcohol consumption, and significant increases in readiness to change and likelihood of using moderate drinking strategies. In qualitative analyses, men appreciated the friendly, non-threatening tone and that the message was straightforward, meaningful, achievable, and was gain-framed - i.e., emphasised the benefits of drinking less rather than the harms of drinking too much. However, the men who did not change their behaviour also identified several barriers to responding in ways encouraged by the message. It would be important to address their views of their drinking as not problematic, as pleasurable, and as socially expected, and also their sense of not feeling empowered to initiate or maintain behaviour change.